E-Loyalty : A study on customer loyalty of internet banking services in Klang Valley / Noor Farihan Elyana Md Noor - Md Noor, Noor Farihan Elyana (2005)
This research is about the customer loyalty toward Internet banking among Klang Valley residents. It focused on the customer loyalty toward Internet banking that is still low and anxious. Nowadays, with the fast development of World Wide Web, most banking institution offered their services through Internet and it becomes a popular alternative of traditional banking. Loyalty is totally different between traditional and online banking. Thus, this research is a research that identify, to find out and to determine the customer loyalty toward Internet banking. The objectives of this research are to identify the relationship between service performance rates and customer satisfaction level with their loyalty towards the internet banking. The sample was randomly selected at the area of Klang Valley. Most of the respondents rate the Internet banking service performance as good and affect their loyalty towards Internet banking. But the Chi-Square test indicates that there is no association between service performance rates and customer loyalty to the Internet banking. It contrasts with the relationship between customer satisfaction level and loyalty where the Chi-Square test indicates that there is relationship between both variables. It means that customer satisfaction level have significant impact on customer loyalty. By improving service performance such as response time and feedback and also customer satisfaction through adding more features and concern on security issues will increase customer loyalty toward internet banking.